NeMeHg, genetically encoded indicator for mercury ions based on mNeonGreen green fluorescent protein and merP protein from Shigella flexneri - Subach, Oksana M.; Piatkevich, Kiryl D.; Subach, Fedor V. (Frontiers in Bioengineering and Biotechnology, 2024)
The detection of mercury ions is an important task in both environmental monitoring and cell biology research. However, existing genetically encoded sensors for mercury ions have certain limitations, such as negative fluorescence response, narrow dynamic range, or the need for cofactor supplementation. To address these limitations, we have developed novel sensors by fusing a circularly permutated version of the mNeonGreen green fluorescent protein with the merP mercury-binding protein from Gram-negative bacteria Shigella flexneri. The developed NeMeHg and iNeMeHg sensors responded to mercury ions with positive and negative fluorescence changes, respectively. We characterized their properties in vitro. Using the developed biosensors, we were able to successfully visualize changes in mercury ion concentration in mammalian cultured cells.